OPTIMASI MASSA RANGKA KENDARAAN ELEKTRIK PENGANGKUT SAMPAH DENGAN SIMULASI METODE ELEMEN HINGGA - Roby Roby; Didi Widya Utama; Noor Eddy (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Residential waste contributes up to 55% of the total volume of urban waste such as in Jakarta. It makes the transport process of residential waste to temprorary landfill site (TPS) that has been existed, less efficient. Transporting waste process with garbage cart is depended on the manpower, while with the garbage truck, the vehicle’s width and the use of fossil fuels are the weaknesses. Thus, the design concept of a waste transport vehicle using electric motor as driving source is made which has the same payload capacity as a garbage cart in general. Garbage payload along with the main components must be strongly supported by the vehicle frame, which incidentally serves as the support vehicle. In this study, discussed the optimization of electric waste transport vehicle with the help of 3-dimensional CAD modelling, then simulated with static loading to obtain the results of the stress, displacement with the maximum value and location, and can assign the payload distribution position. With variable of the beam profile shape and its thickness, then obtained the optimal order forms, which frame weighs as light as possible but still robust in supporting given loads, which is frame with a cylindrical hollow profile with diameter of 60.3 mm and thickness of 4 mm .